Environmental risk assessment and stabilization/solidification of zinc extraction residue: II. Stabilization/solidification - Erdem, Mehmet; Ozverdi, Arzu (Elsevier Science Bv, 2011)
Heavy metal contamination is an important problem that is encountered at many metallurgical sites. Solidification/stabilization is a widely applied remediation technology for heavy metal contamination. In the study, solidification and stabilization of zinc extraction residue containing some heavy metals (e.g. Pb, Zn, Cd, Mn) which can leach using Portland cement, fly ash and lime was examined. Zinc extraction residue was solidified and stabilized with different amounts of Portland cement, fly ash and lime for heavy metal immobilization. Leaching behavior of all solidified/stabilized products was tested by pH dependent batch leaching test, Toxicity Characteristic Leaching Procedure (TCLP) and Synthetic Precipitation Leaching Procedure (SPLP). The results were evaluated in order to determine if the solidified/stabilized products can be disposed of at a landfill site with domestic waste or at a segregated landfill. Mechanical strength decreases with increase in the waste content. Heavy metals in the waste could be considerably immobilized by the solidification/stabilization process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Metallurgical waste; Heavy metal pollution; Zinc; Solidification and stabilization; TCLP